2016
DOI: 10.3233/bir-15045
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic receptor cleavage in the pathogenesis of blood rheology and co-morbidities in metabolic syndrome. Early forms of autodigestion

Abstract: Abnormal blood rheological properties seldom occur in isolation and instead are accompanied by other complications, often designated as co-morbidities. In the metabolic syndrome with complications like hypertension, diabetes and lack of normal microvascular blood flow, the underlying molecular mechanisms that simultaneously lead to elevated blood pressure and diabetes as well as abnormal microvascular rheology and other cell dysfunctions have remained largely unknown. In this review, we propose a new hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 101 publications
(119 reference statements)
1
15
0
Order By: Relevance
“…Hiriart et al [11] have found that hyperinsulinaemia is associated with increased soluble insulin receptors release from hepatocytes, which could lead to higher amounts of insulin bound to this receptor instead of free insulin, which is the biologically active form of the hormone. Schmid-Sch€ onbein and coworker [13,14] have suggested that metabolic syndrome with complications like diabetes, elevated blood pressure as well as abnormal vascular rheology is due to uncontrolled extracellular proteolytic activity that causes receptor cleavage. Schmid-Sch€ onbein and coworker [13,14] have suggested that metabolic syndrome with complications like diabetes, elevated blood pressure as well as abnormal vascular rheology is due to uncontrolled extracellular proteolytic activity that causes receptor cleavage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hiriart et al [11] have found that hyperinsulinaemia is associated with increased soluble insulin receptors release from hepatocytes, which could lead to higher amounts of insulin bound to this receptor instead of free insulin, which is the biologically active form of the hormone. Schmid-Sch€ onbein and coworker [13,14] have suggested that metabolic syndrome with complications like diabetes, elevated blood pressure as well as abnormal vascular rheology is due to uncontrolled extracellular proteolytic activity that causes receptor cleavage. Schmid-Sch€ onbein and coworker [13,14] have suggested that metabolic syndrome with complications like diabetes, elevated blood pressure as well as abnormal vascular rheology is due to uncontrolled extracellular proteolytic activity that causes receptor cleavage.…”
Section: Introductionmentioning
confidence: 99%
“…El Mesallamy et al have found that both obesity and type 2 diabetes are associated with increased serine protease plasma granzyme B, which correlate with inflammation, insulin receptor cleavage and insulin resistance [12]. Schmid-Sch€ onbein and coworker [13,14] have suggested that metabolic syndrome with complications like diabetes, elevated blood pressure as well as abnormal vascular rheology is due to uncontrolled extracellular proteolytic activity that causes receptor cleavage. Delano et al [15] have proposed that a mechanism of action of insulin resistance in obesity is insulin receptor cleavage by increased proteinase activity, especially MMP-1 and MMP-9.…”
Section: Introductionmentioning
confidence: 99%
“…Elevation of plasma protease activity was shown to be associated with diet-induced obesity and insulin resistance or chronic inflammation [3][4][5][6][7][8][9] . Badeanlou et al reported that diet-induced insulin resistance required protease-activated receptor 2 signaling activation 3 .…”
mentioning
confidence: 99%
“…Furthermore, α1-antitrypsin has been shown to prevent type 1 diabetes development, prolong islet allograft survival, and inhibit pancreatic β-cell apoptosis in vivo 8 . Chronic inflammation-induced proteolytic matrix metalloproteinases cleave the extracellular domains of insulin receptors, induce soluble insulin receptor-α in human plasma, and promote insulin resistance 9 . Interestingly, the recent evidence showed that the soluble insulin-receptor ectodomain is elevated in the plasma of patients with diabetes 10 , and the serine protease granzyme B is an inflammatory marker related to insulin receptor cleavage in human obesity and type 2 diabetes mellitus 11 .…”
mentioning
confidence: 99%
“…For example, it is not clear what role protease-dependent receptor cleavage (Schmid-Schonbein, 2016; Mazor & Schmid-Schonbein, 2015) might play in postischemic EDD dysfunction. Moreover, interesting recent work has demonstrated that pentraxin 3, a soluble pattern recognition receptor that plays an important role in innate immune responses, induces EDD dysfunction via a P-selectin/MMP-dependent pathway that may feed into our hypothesized mechanism (Carrizzo, Lenzi, Procaccini, Damato, Biagioni, Ambrosio et al, 2015).…”
Section: Summary and Future Directionsmentioning
confidence: 99%